The Effect of Using The Think Pair Share Learning Model To Enhance The Capability to Comprehending The German Text - Jolanda Tomasouw; Juliaans E. R Marantika (Universitas Pattimura, 2021)
This study aims to see the effect of using the Think Pair Share learning model on the ability to understand the text in the Arbeit am Text course. The TPS learning model is a cooperative learning model that can increase learner participation in the learning process. The sample for this research was the fifth-semester students of the 2019/2020 academic year with 22 students as respondents. This study consists of two variables, namely the independent variable and the dependent variable. The independent variable is the TPS learning model, while the dependent variable is the ability to understand the text. The method used in this research is an experimental method using data collection techniques Pre and Post Test. The data were then analyzed using the T-Test. With a significant level of Î± = 0.05, the results of the analysis show that the t count is greater than the t table, namely 7.93 â‰¥ 1.72. This shows that there is a significant effect of using the TPS learning model on students' ability to understand the text. Based on the results, it is concluded that the TPS learning model contributes to the improvement of students' ability to understand German language texts in the Arbeit am Text course